Parental strategies to promote theory of mind development in autistic children of color - Modirrousta, Annahita; Harris, Yvette R. (Frontiers in Psychology, 2024)
Introduction: Autism Spectrum Disorder is characterized by an impaired ability to take other people's perspectives, which is known as theory of mind. However, little is known about how theory of mind exhibits itself in autistic children of color and how parents foster their child's developmental skills in communities of color. Methods: Two interviews were created to assess how parents appraise their child's developmental skills and help their child grow: a perspective-teaching interview and a general developmental skills interview. Four families participated in the study; three children were African American or mixed, while one had an Asian mother. Parents were asked how their child exhibited various developmental skills and how they helped their child with those milestones. Results: Parents pointed at similar delays in theory of mind and other developmental skills, such as turn-taking and reading faces. They also provided similar strategies to teach those abilities, such as modeling and reinforcements. Several insights and common themes were found regarding autistic behaviors their children expressed and how those affected their parenting experiences. Discussion: These findings allow for a better understanding of parents' experiences raising autistic children of color; future research could expand on their stories and create interventions tailored to these underrepresented communities.